Analisis Pelaksanaan Layanan Konseling Individu Melalui Problem Check List dan Catatan Anekdot di SMK Mandiri Tembung - Harahap, Ade Chita Putri; Siregar, Afnita Marni; Ikhsan, Bastothum; Prayetno, Miftah Suhaila; Ramadhan, Muhammad Fiqri; Abdillah, Rizky; Thasfa, Saida Amini (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
School as an educational institution and is a means in the context of these educational goals. In the school environment students are required to comply with the rules and regulations that exist in school. The purpose of this study was to determine individual counseling services in problem check lists and anecdotal notes at Tembung Mandiri Vocational School. This study uses a descriptive qualitative research method. Data collection techniques used in this study by way of observation, interviews, and documentation. The research subjects in this study were counseling teachers and class X students of Light Vehicle Engineering. The results of this study indicate that the implementation of individual counseling services in problem check lists and anecdotal notes at Mandiri Tembung Vocational High School indicates that the counseling teacher has provided individual counseling services to students who experience individual problems. Keywords: counseling services, problem check lists and anecdotal notes